2007
DOI: 10.1002/art.22402
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of inflammation and structural damage in experimental arthritis through molecular targeted therapy with PPI‐2458

Abstract: Methods. Arthritis was induced in rats by administration of PG-PS, causing tarsal joint swelling and histopathologic changes characteristic of rheumatoid arthritis (RA). PPI-2458, a potent irreversible methionine aminopeptidase type 2 inhibitor, was administered orally every other day at 1, 5, or 10 mg/kg.Results. In an in vitro osteoclastogenesis model, PPI-2458 potently inhibited osteoclast differentiation and bone resorption. In the rat PG-PS arthritis model, PPI-2458 afforded significant protection against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…This study of the metabolism of PPI-2458 was driven by observations of efficacy in animal models for cancer (Cooper et al, 2006;Hannig et al, 2006) and rheumatoid arthritis (Hannig et al, 2007;Lazarus et al, 2008) after oral dosing, despite apparent low oral bioavailability of the parent compound. As a first step toward characterization of PPI-2458 metabolism in vivo, we studied the effects of treatment with liver microsomal preparations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study of the metabolism of PPI-2458 was driven by observations of efficacy in animal models for cancer (Cooper et al, 2006;Hannig et al, 2006) and rheumatoid arthritis (Hannig et al, 2007;Lazarus et al, 2008) after oral dosing, despite apparent low oral bioavailability of the parent compound. As a first step toward characterization of PPI-2458 metabolism in vivo, we studied the effects of treatment with liver microsomal preparations.…”
Section: Discussionmentioning
confidence: 99%
“…PPI-2458, [(3R,4S,5S,6R)-5-methoxy-4-[(2R,3R)-2-methyl-3-(3-methylbut-2-enyl) oxiran-2-yl]-1-oxaspiro[2.5]octan-6-yl] N-[(2R)-1-amino-3-methyl-1-oxobutan-2-yl]carbamate, differs from fumagillin in that the polyolefinic chain is replaced by a carbamoyl-linked D-valinamide moiety (Olson et al, 2003;Arico-Muendel et al, 2009). PPI-2458 has demonstrated efficacy in rodent models for non-Hodgkin lymphoma (Cooper et al, 2006), melanoma , and arthritis (Bernier et al, 2004;Bainbridge et al, 2007;Hannig et al, 2007;Lazarus et al, 2008;Brahn et al, 2009;Ashraf et al, 2010;Ashraf et al, 2011). In preclinical studies, PPI-2458 was approximately equipotent in several in vivo efficacy models by both oral and parenteral routes of administration, despite an apparently modest oral bioavailability (F% = 6) (AricoMuendel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Sustained inhibition of angiogenesis that is begun during the induction, or at the onset, of synovitis can reduce inflammation and joint damage (21,23,27,37,38). However, adverse effects of long-term angiogenesis inhibition on physiologic blood vessel growth may outweigh the therapeutic benefit in chronic inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This is most likely because of PPI-2458 inhibition of human fibroblast-like synoviocyte proliferation (Bernier et al, 2004) in pannus growth and contributes to migration of inflammatory cells from the periphery (Bernier et al, 2005). Furthermore, previous in vitro work has demonstrated that PPI-2458 inhibits osteoclast precursor differentiation into multinucleated osteoclasts (Hannig et al, 2007;Lazarus et al, 2008), possibly by inhibiting fibroblastlike synoviocytes that release receptor activator of nuclear factor-B ligand, which promotes osteoclast formation and activation (Teitelbaum, 2000;Bernier et al, 2004;Wu et al, 2005;Hannig et al, 2007). Such an effect would alter the balance between bone formation and bone resorption (Campagnuolo et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…1) that targets MetAP-2 and inhibits endothelial cell proliferation (Bernier et al, 2005). This compound has been shown to reduce swelling in a peptidoglycan-polysaccharide-induced model when administered subcutaneously or orally (Bernier et al, 2004;Hannig et al, 2007) and to suppress murine collagen-induced arthritis (CIA) (Bainbridge et al, 2007). The current study evaluates PPI-2458 in the rat CIA RA model of autoimmune chronic inflammatory arthritis (Trentham et al, 1977).…”
mentioning
confidence: 99%